Trade Credit and Bank Credit : Evidence from Recent Financial Crises - Love, Inessa; Preve, Lorenzo A.; Sarria-Allende, Virginia (World Bank, Washington, DC, 2012)
The authors study the effect of financial crises on trade credit in a sample of 890 firms in six emerging economies. They find that although provision of trade credit increases right after the crisis, it consequently collapses in the following months and years. The authors observe that firms with weaker financial position (for example, high pre-crisis level of short-term debt and low cash stocks and cash flows) are more likely to reduce trade credit provided to their customers. This suggests that the decline in aggregate credit provision is driven by the reduction in the supply of trade credit, which follows the bank credit crunch. The results are consistent with the "redistribution view" of trade credit provision, in which bank credit is redistributed by way of trade credit by the firms with stronger financial position to the firms with weaker financial stand